Electability of Presidential and Vice Presidential Candidates Among Gen Z in the 2024 Presidential Election - Sani, Zara Aprilia; Abadi, Totok Wahyu; Febriana, Poppy; Tze Wui, Kenneth Lee (Communicatus: Jurnal Ilmu komunikasi, 2024)
Social media has become a dominant factor in shaping the political behaviour of Generation Z, especially in the 2024 Presidential Election. This study aims to analyze the influence of information exposure, news content, candidate electability, and social media on the behaviour of Generation Z voters. With an explanatory quantitative approach, data were collected through questionnaires filled out by 160 University of Muhammadiyah Sidoarjo students, using the multistage cluster random sampling method. The research variables were measured using a Likert scale and tested using multiple linear regression based on SPSS 25. The study results showed that, partially, news content, candidate electability, and social media significantly influenced the behaviour of Generation Z voters, with the most significant contribution coming from social media (30.7%). In contrast, information exposure did not have a significant influence. Simultaneously, the four variables contributed 55.2% to voter behaviour. The study also found that although Generation Z actively uses social media, they tend to be sceptical of political information. In conclusion, social media, candidate electability, and news content are the main factors that influence Generation Z's political behaviour. Therefore, designing a creative and fact-based social media campaign strategy is essential to increase healthy political participation.